1981
DOI: 10.1063/1.441594
|View full text |Cite
|
Sign up to set email alerts
|

Continuous wave intracavity dye laser spectroscopy. II. A parametric study

Abstract: The sensitivity enhancement of cw intracavity dye laser spectra of I2 and of water vapor has been measured for four dye laser tuning systems, two cavity lengths, and a wide range of pumping powers. The longitudinal mode structure of the dye laser has also been examined. The sensitivity enhancement increases with the bandpass of the dye laser tuning element and is independent of the cavity length. It is only weakly dependent on pumping power except near threshold, where it climbs steeply. The experimental resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…There are several informative reviews of ICLAS and its applications (Harris, 1984;Atkinson, 1986Atkinson, , 2002Toschek and Baev, 1987;Baev et al , 1999;Romanini, 1999). A selection of additional publications concerns ICLAS instrumentation (H ä nsch et al , 1972;Brunner et al , 1979;Harris and Weiner, 1981;Garnache et al , 2000;Scherer et al , 2009;Ueda et al , 2012) and its applications, e.g., in studies of transient molecular species (Sheehy and Steinfeld, 2005) and in high-resolution molecular spectroscopy (Oka, 1982;Scherer et al , 1983). By using a multimode laser with a homogeneously broadened gain bandwidth that exceeds the absorption linewidth, such that laser gain compensates broadband cavity loss, it is possible for ICLAS to attain very high sensitivity (Toschek and Baev, 1987).…”
Section: Intracavity Laser Absorption Spectroscopy (Iclas)mentioning
confidence: 98%
“…There are several informative reviews of ICLAS and its applications (Harris, 1984;Atkinson, 1986Atkinson, , 2002Toschek and Baev, 1987;Baev et al , 1999;Romanini, 1999). A selection of additional publications concerns ICLAS instrumentation (H ä nsch et al , 1972;Brunner et al , 1979;Harris and Weiner, 1981;Garnache et al , 2000;Scherer et al , 2009;Ueda et al , 2012) and its applications, e.g., in studies of transient molecular species (Sheehy and Steinfeld, 2005) and in high-resolution molecular spectroscopy (Oka, 1982;Scherer et al , 1983). By using a multimode laser with a homogeneously broadened gain bandwidth that exceeds the absorption linewidth, such that laser gain compensates broadband cavity loss, it is possible for ICLAS to attain very high sensitivity (Toschek and Baev, 1987).…”
Section: Intracavity Laser Absorption Spectroscopy (Iclas)mentioning
confidence: 98%
“…Amplitude and frequency jitter in the output of the dye laser probably originate from flow instabilities, including bubbles, within the dye stream and seemed to worsen with extended running time. 30 It is of interest to analyze the evolution of both the where total laser intensity, generation time, losses in the optical cavity, spectral frequency (cm-1) frequency at line center of laser gain profile (cm-1 ), and initial bandwidth (cm-1).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several treatments of signal collection in LEI spectrometry have been useful additions to the general theory (3,4). Investigators have reported interferences with LEI spectrometry in a series of papers (5)(6)(7)(8)(9)(10) 0003-2700/85/0357-0016$01.50/0 © 1984 American Chemical Society…”
mentioning
confidence: 99%